A survey of recent theoretical results for time series models with GARCH errors - W. K. Li; Shiqing Ling; Michael MacAleer (Osaka University, Institute of Social and Economic Research (ISER), 2001)
This paper provides a review of some recent theoretical results for time series models with GARCH errors, and is directed towards practitioners. Starting with the simple ARCH model and proceeding to the GARCH model, some results for stationary and nonstationary ARMA-GARCH are summarized. Various new ARCH-type models, including double threshold ARCH and GARCH, ARFIMA-GARCH, CHARMA and vector ARMA-GARCH, are also reviewed.
Keywords: 330; Zeitreihenanalyse; ARCH-Modell; Theorie